DIGITAL INVESTIGATION OF LAMNIFORM SHARK VERTEBRAE FROM THE SIBILLINI MTS. (NORTHERN APENNINES, ITALY) (Rivista italiana di Paleontologia e Stratigrafia, 2024)
During the sampling of a stratigraphic section along the shore of the Fiastra Lake (Carg Project - Sheet 313 “Camerino” of the Geological Map of Italy at 1:50 000 scale), a small rock boulder with partially exposed bony material was discovered at the base of a small cliff at the northern termination of the Sibillini Mts. In this area, the classical facies of Umbria-Marche stratigraphic succession are well exposed. The Oligocene-Miocene portion of the succession is represented by the ~200 m-thick Scaglia Cinerea Formation, passing upwards to the ~100 m-thick Bisciaro Formation. The microfossil assemblage has allowed the specimen to be constrained to the lower Burdigalian. The skeletal remains were examined using a CT-SCAN, a non-invasive method that has proven to be highly performing. The analysis revealed some articulated vertebrae, deformed by lithostatic compaction, which are attributed to a shark of the Order Lamniformes. Subsequently, the vertebrae were digitally isolated, extracted from the surrounding matrix, and rendered into three-dimensional prints. Through digital retro-deformation, the body length of the lamniform shark was estimated to be approximately 4 metres. Further considerations on the vertebrae allowed us to infer that the studied shark had similarities to either Isurus oxyrinchus Rafinesque, 1810 or Carcharodon carcharias Linnaeus, 1758. The development of a dead-fall microbial community likely facilitated the preservation of the vertebrae. The studied specimen represents the first occurrence of a lamniform shark in the Lower Miocene of the Umbria-Marche Domain and represents one of the very rare recorded occurrences of lamniforms from the Lower Miocene of Italy.